Beliefs Related to Mental Illness Stigma Among California Young Adults - Collins, Rebecca L. (RAND Corporation, 2014)
Report examines mental illness stigma and related beliefs among young adults in California, especially whether levels of stigma are higher or lower than those observed in older adults.